Perlindungan Terhadap Pelanggaran Hak Asasi Manusia kepada Pekerja Perempuan Berhijab dalam Sektor Industri - Adila Nida Ahmada (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Human rights (HAM) are rights that every human being must have, without which it is impossible for them to live as human beings. Employers who enforce regulations prohibiting female workers from wearing the hijab can be considered religious discrimination against their employees. One of the clothes that is synonymous with women is the hijab, which means women are considered unable to carry out their activities freely. As a result, in some places, women wearing the hijab are considered to be discriminated against. The aim of this research is to find out what forms of discrimination there are against female workers who wear the hijab and the efforts that female workers can make to eliminate discrimination in wearing the hijab in the workplace, as well as the legal consequences of implementing it. the prohibition. The results of this research are that the government must be more strict in imposing sanctions on companies that provide regulations prohibiting female workers from wearing the hijab.